2009
DOI: 10.1002/iroh.200811107
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Distributions of Rotifers in Xiangxi Bay of the Three Gorges Reservoir, China

Abstract: The rotifer community exhibited a patchy distribution, with significant heterogeneity observed along the longitudinal axis. All rotifer communities could be divided into three groups, corresponding to the riverine, the transition and the lacustrine zone, respectively. IntroductionZooplankton heterogeneity and community structure at a range of spatial and temporal scales is an important focus of aquatic ecological research (CLARK et al., 2001). Studies on temporal variations in zooplankton distribution are comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…Following the above point of view, the present study can take an applied perspective to the improvement of ecological observation programs for TGR and the reduction of long-term monitoring costs. Since TGR is one of the largest human-made lakes in the world, there has been much more attention paid to the potential change in the aquatic ecosystem after the impoundment of TGR (e.g., Cai and Hu 2006;Ye et al 2007;Shao et al 2008;Zhou et al 2009;Zhang et al 2010). Most aquatic researchers and TGR managers hope to infer ecological trends of the reservoir from the accumulation of local site-specific trends because it is very hard to carry out the full-scale observations in the giant dendritic reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…Following the above point of view, the present study can take an applied perspective to the improvement of ecological observation programs for TGR and the reduction of long-term monitoring costs. Since TGR is one of the largest human-made lakes in the world, there has been much more attention paid to the potential change in the aquatic ecosystem after the impoundment of TGR (e.g., Cai and Hu 2006;Ye et al 2007;Shao et al 2008;Zhou et al 2009;Zhang et al 2010). Most aquatic researchers and TGR managers hope to infer ecological trends of the reservoir from the accumulation of local site-specific trends because it is very hard to carry out the full-scale observations in the giant dendritic reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…The diatom bloom in the Xiangxi Bay seemed to accelerate the densities of rotifers although with several days of lag. This indicates that phytoplankton is the primary food resource for rotifers (Guiral et al, 1994;Yoshida et al, 2003;Zhou et al, 2009). It has been reported that in spring the metabolism and production of zooplankton could be increased by the increasing food supply (Montagnes & Lessard, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…P. truncatum is reported as thermophilic specimen (Koste 1978), and its embryonic development occurs at high temperatures, and this period continues for a long time (Edmondson 1960). P. truncatum was reported from various areas in the world including; Russia (Telesh 1995), Canada (Swadling et al 2000), China (Lin et al 2003;Zhaou et al 2009 Kehayias et al 2008), and North America (Barbiero and Warren 2011), except Turkey which is located in Palearctic region. Also, it has been a subject of several studies (e.g.…”
Section: Discussionmentioning
confidence: 99%